2018
DOI: 10.9734/arrb/2018/41014
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Chlorophyll Fluorescence, Leaf Gas Exchange and Phytochemicals of Centella asiatica Exposed to Salinity Stress

Abstract: Aims: This study was conducted to investigate the effect of salinity by using a different concentration of sodium chloride (NaCl), on growth, chlorophyll fluorescence and secondary metabolites production of Centella asiatica. Study Design: Centella asiatica plants were exposed to four different concentration of sodium chloride (0, 50, 100 and 150 mM). This research was conducted using a randomized complete block design 4 x 3 with three replications for each treatment and each treatment consists of 12 plants re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…While at lower salinity level (60 mM) reduction of 20% was observed. Similar studies of reduction in shoot fresh weight of shoot was reported by Ors et al [20] in tomato, Dolatabadian et al [21] in soybean, and reduction in shoot dry weight by Dong et al [22] in sugarbeet, Ibraham et al [23] in Indian Pennywort.…”
Section: Resultssupporting
confidence: 78%
“…While at lower salinity level (60 mM) reduction of 20% was observed. Similar studies of reduction in shoot fresh weight of shoot was reported by Ors et al [20] in tomato, Dolatabadian et al [21] in soybean, and reduction in shoot dry weight by Dong et al [22] in sugarbeet, Ibraham et al [23] in Indian Pennywort.…”
Section: Resultssupporting
confidence: 78%
“…The overall cultivation condition is summarized in Table 1. These targeted LED combinations and EC levels were selected based on the findings in [43][44][45][46] and [47][48][49][50][51], respectively. A wireless sensor network (XBee-Pro, Digi, Hopkins, MN, USA) was used to monitor the ambient environmental parameters and control the relevant actuators, as detailed by [52].…”
Section: Plant Factory Preparation and Operationmentioning
confidence: 99%
“…In vitro salt stress has been researched in many medicinal plants like Centella asiatica (L.) Urb., Catharanthus roseus (L.) G. Don, Trigonella foenum-graecum L., Carthamus tinctorius L. etc. (Jaleel et al, 2008;Gengmao et al, 2015;Sahari et al, 2016;Ibrahim et al, 2018). To adapt unfavorable stress conditions, the salt tolerant plants produce different secondary metabolites to serve cellular functions essential for physiological processes.…”
Section: Introductionmentioning
confidence: 99%